Midterm Experience of Ipsilateral Axillary-Axillary Arteriovenous Loop Graft as Tertiary Access for Haemodialysis - J. P. Hunter; M. L. Nicholson (Journal of Transplantation)
Objectives. To present a series of ipsilateral axillary artery to axillary vein loop arm grafts as an alternative vascular access procedure for haemodialysis in patients with difficult access. Design. Retrospective case series. Methods. Patients who underwent an axillary loop arteriovenous graft from September 2009 to September 2012 were included. Preoperative venous imaging to exclude central venous stenosis and to image arm/axillary veins was performed. A cuffed PTFE graft was anastomosed to the distal axillary artery and axillary vein and looped on the arm. Results. 25 procedures were performed on 22 patients. Median age was 51 years, with 9 males and 13 females. Median number of previous access procedures was 3 (range 0–7). Median followup was 16.4 months (range 1–35). At 3 months and 1 year, the primary and secondary patency rates were 70% and 72% and 36% and 37%, respectively. There were 11 radiological interventions in 6 grafts including 5 angioplasties and 6 thrombectomies. There were 19 surgical procedures in 10 grafts, including thrombectomy, revision, repair for bleeding, and excision. Conclusions. Our series demonstrates that the axillary loop arm graft yields acceptable early patency rates in a complex group of patients but to maintain graft patency required high rates of surgical and radiological intervention, in particular graft thrombectomy.